Peningkatan Kesadaran Sosial Peserta Didik Fase F Kelas Xii-6 SMA Pangudi Luhur Van Lith Tahun Pelajaran 2024/2025 Melalui Model Project Based Learning (PjBL) pada Materi Keterlibatan Umat Katolik dalam Pembangunan Bangsa Indonesia - Heribertus Eko Prasetyo (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
Catholic Religious Education plays a strategic role in shaping learners who are not only intellectually intelligent but also possess deep spiritual consciousness and high social awareness. However, classroom instruction is still predominantly characterized by theoretical approaches and rote memorization of theological concepts, offering limited opportunities for students to gain real-life experiences in understanding the relevance of Church teachings in societal and national life. This study aims to analyze the implementation of the Project-Based Learning (PjBL) model in enhancing the social awareness of Grade XII-6 students at SMA Pangudi Luhur Van Lith Muntilan, particularly in comprehending the involvement of Catholics in nation-building within Indonesia. The research employed Classroom Action Research (CAR), utilizing cycles of planning, action, observation, and reflection. The findings indicate that the application of PjBL successfully improved students' understanding of Catholic Social Teachings and increased their active participation in faith-based social actions. Challenges in implementing PjBL, such as time constraints and limited communication resources in a boarding school environment, were addressed through careful planning and adaptive learning strategies. This study contributes to the development of more contextual and applicable methods of religious education, fostering learners who not only cognitively understand Church teachings but also actualize their faith through concrete actions for the common good.